Effect of standard heat treatment on the microstructure and mechanical properties of hot isostatically pressed superalloy inconel 718 - Rao G.A.; Kumar M.; Srinivas M.; Sarma D.S. (My University, 2025)
Ni-Fe base superalloy, Inconel 718, was processed through powder metallurgy (P/M) hot isostatic pressing (HIP) route. In order to balance the strength and ductility, the HIPed material was given the standard heat treatment, viz. solution treatment at 980 °C for 1 h/water quenched (WQ) to room temperature and a two-step ageing treatment consisting of 720 °C for 8 h/furnace cooling (FC) at 55 °C h-1 to 620 °C and holding at 620 °C for 8 h before air cooling (AC) to room temperature. Optical microscopy and scanning electron microscopy (SEM) studies on the heat treated alloy have shown a homogeneous microstructure with fine grain size (25 μm) along with the presence of prior particle boundary (PPB) networks. Transmission electron microscopy (TEM) on the heat treated material has revealed the presence of oxides, MC carbides and δ-precipitates at the grain boundaries and a uniform precipitation of fine γ′ and γ′ strengthening phases in the matrix. Tensile and stress rupture tests were performed on the heat treated material. While the yield strength (YS) and ultimate tensile strength (UTS) of the HIPed and heat treated alloy at room temperature and 650 °C were comparable to those of conventionally processed wrought IN 718, its ductility was lower. The stress rupture life of the HIPed alloy improved marginally due to heat treatment and met the minimum specification requirement of life hours but the rupture ductility was found to be inferior to that of the wrought material. The fractography of the failed samples has revealed the transgranular ductile mode of fracture in the as-solution treated alloy, while intergranular mode of failure with the decohesion of PPBs occurred more predominantly in the aged condition. This change of fracture mode with ageing treatment shows the ductility dependence on the relative strength of the matrix and PPBs. The TEM studies on the deformed alloy have revealed that the brittle oxides and carbides at the prior particle boundaries coupled with the fine γ″ and γ′-precipitates in the matrix are responsible for low ductility at 650 °C. The investigations of the present study have led to better understanding of the structure-property relationships in HIP+heat treated alloy 718 and suggest that the standard heat treatment recommended for wrought IN 718 is not suitable for HIPed alloy and has to be modified to realise optimum properties. © 2003 Elsevier Science B.V. All rights reserved.